1993
DOI: 10.1007/bf00590042
|View full text |Cite
|
Sign up to set email alerts
|

A bioresorbable urethral stent

Abstract: The aim of the present study was to examine the suitability of biodegradable polymers as materials for a urethral stent. A new urethral stent made of biodegradable self-reinforced poly-L-lactide (SR-PLLA) was implanted in 16 male rabbits after urethrotomy. Seven stents of stainless steel served as controls. The dimensions of the two types of stents were identical: length 15 mm, diameter 8.2 mm. The mechanical construction was a helical spiral. The SR-PLLA spiral was sustained with three microspirals, and the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
3

Year Published

1994
1994
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(37 citation statements)
references
References 9 publications
0
34
0
3
Order By: Relevance
“…IS Although some of these polypoid growths coalesce over the metal, the stent is not truly incorporated in the wall thickness because mucosal cells are still present on the ablu minal side of the stent. 16 Recently a bio resorbable urethral stent has been investi gated in rabbits by Kemppainen et al 17 The bioresorbable urethral stent is made of biodegradable self-reinforced poly-L-lactide to achieve an active initial tissue reaction and better tissue penetration. As the tissue reaction around the bioresorbable stent material is minimal, the chances of stenosis due to exuberant fibrotic proliferation re quiring endoscopic treatment which has been reported with the self-expandable urethral stent (wallstent) may be diminished in case of the bioresorbable stent.…”
Section: Discussionmentioning
confidence: 99%
“…IS Although some of these polypoid growths coalesce over the metal, the stent is not truly incorporated in the wall thickness because mucosal cells are still present on the ablu minal side of the stent. 16 Recently a bio resorbable urethral stent has been investi gated in rabbits by Kemppainen et al 17 The bioresorbable urethral stent is made of biodegradable self-reinforced poly-L-lactide to achieve an active initial tissue reaction and better tissue penetration. As the tissue reaction around the bioresorbable stent material is minimal, the chances of stenosis due to exuberant fibrotic proliferation re quiring endoscopic treatment which has been reported with the self-expandable urethral stent (wallstent) may be diminished in case of the bioresorbable stent.…”
Section: Discussionmentioning
confidence: 99%
“…anterior urethra of the rabbit [1]. The SR-PGA spiral stent has been used in combination with visual laser…”
Section: Methodsmentioning
confidence: 99%
“…Kemppainen et al 29 placed biodegradable self-reinforced stent made of poly-L-lactide (SR-PLLA) in 16 male rabbits after urethrotomy. In this report, authors concluded biodegradable SR-PLLA is promising material for a urethral stent to prevent re-stenosis of urethral strictures.…”
Section: Bioabsorbable Stentmentioning
confidence: 99%